2004
DOI: 10.1124/mol.104.002600
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Mitochondrial Aldehyde Dehydrogenase Activity: A Comparison of Pentaerythritol Tetranitrate with Other Organic Nitrates

Abstract: Mitochondrial aldehyde dehydrogenase (ALDH-2) was recently identified to be essential for the bioactivation of glyceryl trinitrate (GTN). Here we assessed whether other organic nitrates are bioactivated by a similar mechanism. The ALDH-2 inhibitor benomyl reduced the vasodilator potency, but not the efficacy, of GTN, pentaerythritol tetranitrate (PETN), and pentaerythritol trinitrate in phenylephrine-constricted rat aorta, whereas vasodilator responses to isosorbide dinitrate, isosorbide-5-mononitrate, pentaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
167
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 37 publications
14
167
1
2
Order By: Relevance
“…There is evidence that oxidants can inactivate ALDH-2 directly and induce nitrate tolerance Wenzel et al, 2007). Oxidative stress may contribute directly to nitroglycerin tolerance, either by oxidative inhibition of ALDH-2 or perhaps by oxidizing key enzyme cofactors (Chen et al, 2002;Sydow et al, 2004;Daiber et al, 2004;Munzel et al, 2005). The present study confirmed previous observations that pretreatment of the isolated rat thoracic aorta with ALDH-2 inhibitors significantly attenuated the vasodilation and depressor effect of nitroglycerin (Chen et al, 2002;Sydow et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…There is evidence that oxidants can inactivate ALDH-2 directly and induce nitrate tolerance Wenzel et al, 2007). Oxidative stress may contribute directly to nitroglycerin tolerance, either by oxidative inhibition of ALDH-2 or perhaps by oxidizing key enzyme cofactors (Chen et al, 2002;Sydow et al, 2004;Daiber et al, 2004;Munzel et al, 2005). The present study confirmed previous observations that pretreatment of the isolated rat thoracic aorta with ALDH-2 inhibitors significantly attenuated the vasodilation and depressor effect of nitroglycerin (Chen et al, 2002;Sydow et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…Proposed mechanisms of tolerance include: (1) depletion of critical sulfhydryl groups [5], (2) desensitization of guanylyl cyclase [6], (3) impaired bioconversion of nitrates leading to diminished NO-release [7], (4) reduced generation of NO from nitrates [8], (5) increased activity of the cyclic GMP phosphodiesterase, which decreases cyclic GMP levels [9] and (6) a free radical hypothesis proposing increased oxidant stress [10,11]. Nitroglycerininduced reactive oxygen species also inhibit the activation of nitroglycerin by thiol oxidation of mitochondrial aldehyde dehydrogenase which might explain why nitroglycerin elicits mitochondrial superoxide formation and nitrate tolerance [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a key enzyme involvement of nitroglycerin and nitrates biotransformation, namely the mitochondrial aldehyde dehydrogenase (ALDH 2), is inhibited by reactive oxygen species (ROS) which in addition, can degrade nitric oxide (Wenzel et al, , 2009bDaiber et al, 2004Daiber et al, , 2009bSydow et al, 2004). Therefore, it would be interesting to study the benefit of antioxidants in preventing nitrate tolerance development.…”
Section: Discussionmentioning
confidence: 99%
“…In the current state of knowledge, oxidative stress is a major cause of this phenomenon (Fadel et al, 2012;Oelze et al, 2010;Daiber et al, 2004;Mollnau et al, 2006). Thus, our hypothesis derives from the antioxidant capacity of compounds to reduce or prevent vascular tolerance to nitrates, by reducing oxidative stress.…”
Section: Introductionmentioning
confidence: 99%